Preparation and Evaluation of a Budesonide Nanosuspension for Inhalation Use - Chandra Shekhara Rao G,; T. Deborah paripuranam,; Bhupen Kumar Baruah,; Anirudh Padiyar,; Dr Pankaj Gupta,; Yogesh Matta,; Khanapure Priti Parmeshwar,; Dowluru SVGK Kaladhar,; Sweety Lanjhiyana,; Sanjay Kumar Lanjhiyana, (The Bioscan, 2024)
The development and testing of an inhalation-ready budesonide nanosuspension are the primary areas of investigation in this work. Budesonide, ethanol, medium-chain triglycerides, and polysorbate 80 were the main ingredients in the nanosuspension, which had a particle size of around 10.9 nm. Utilizing jet and vibrating mesh nebulizers, in vitro evaluations were carried out to contrast the aerodynamic characteristics and aerosol production of the newly created nanosuspensions (NE250 and NE500) with those of the conventional budesonide suspension formulations (P250 and P500). The results showed that the nanosuspensions were far more efficient at delivering the medicine than the usual formulations, with more drug caught in the inhalation filters and less residue left in the nebulizer chamber (p<0.05). Furthermore, results from aerodynamic particle size studies demonstrated improved nanosuspensions performance, with a higher percentage of particles smaller than 5 μm—particles that are better suited for deep lung deposition. Based on these results, budesonide nanosuspensions may be a better option than inhalation treatment for treating respiratory disorders.